2022
DOI: 10.1007/s12178-022-09793-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultrasound in the Evaluation of Elbow Medial Ulnar Collateral Ligament Injuries in Throwing Athletes

Abstract: Purpose of Review Although ultrasound (US) imaging is commonly used to evaluate the elbow medial ulnar collateral ligament (mUCL) in throwing athletes, significant technical heterogeneity exists in the published literature and in practice. This has resulted in variable and often ambiguous US diagnostic criteria for mUCL injury. This review summarizes the literature on sonographic evaluation of the mUCL and outlines recommendations for consistent descriptive terminology, as well as future clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Finally, ligament and tendon injuries could also be among the causes of EP [42][43][44][45]. In some clinical medical studies and anatomical literature, baseball players with elbow injures typically require surgical rehabilitation [44,46]. Therefore, for EP swimmers identified as experiencing critical pain in this study, we recommend further medical examinations to mitigate the risk of ligament and tendon injuries exacerbating their EP condition.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, ligament and tendon injuries could also be among the causes of EP [42][43][44][45]. In some clinical medical studies and anatomical literature, baseball players with elbow injures typically require surgical rehabilitation [44,46]. Therefore, for EP swimmers identified as experiencing critical pain in this study, we recommend further medical examinations to mitigate the risk of ligament and tendon injuries exacerbating their EP condition.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, we suggest that swimming teams and clubs at all levels should consider implementing "periodization theory" as the training management principle to address deficiencies, which can provide athletes with maximum rest during busy training schedules [41]. Finally, ligament and tendon injuries could also be among the causes of EP [42][43][44][45]. In some clinical medical studies and anatomical literature, baseball players with elbow injures typically require surgical rehabilitation [44,46].…”
Section: Discussionmentioning
confidence: 99%
“…The utility of stress ultrasound imaging (SUS) has been shown to improve diagnostic accuracy of UCL injuries. Objectively, data has revealed that a side to side difference of more than 1 millimeter or a dominant stress versus nonstress difference of 2.4 millimeters indicate UCL tears requiring surgical intervention (25). Thus, one must consider that if PRP is used in a patient with a partial UCL tear but has not had a SUS completed to assess for UHJ laxity, healing and RTP success rates may be inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,16,27 Dynamic stress ultrasound (SUS) is a reliable tool for evaluating the structure of the UCL and determining injury. 6,10,11,13,15,28,31 The UCL of the dominant arm in pitchers is thicker and has increased laxity compared with the contralateral elbow on SUS. 2,10,19,29 Although SUS has been used to evaluate the risk of increased pitch count and pitch volume on the change in UCL morphology, to our knowledge, no study has investigated SUS findings of the UCL in professional baseball players with respect to their draft position in the MLB draft.…”
mentioning
confidence: 99%